Transforming Multicultural Islamic Curriculum for Religious Moderation and Global Peace - Syaiful Amin; Jamaluddin Akbar; Tri Wahyu Ramdhan; M. Holil; Jimmy Malintang (Universitas Pahlawan Tuanku Tambusai, 2026)
D Amid increasing ideological polarization and global extremism, Islamic education plays a crucial role in cultivating peace. Although prior research has extensively explored the theological concepts of moderation (wasathiyah), current literature remains trapped within rigid epistemic dichotomies. The critical research gap systematically overlooked by previous studies is the lack of operational integration between the Independent Curriculum (Kurikulum Merdeka) reforms in formal schools which are often studied in isolation as technical-administrative state instruments and the organic ecosystem of traditional Islamic boarding schools (pesantren), which are frequently romanticized in a partial manner. Furthermore, a conceptual void persists regarding the operationalization of an inclusive curriculum that bridges classical sufistic ethics with 21st-century digital media resilience. This study is required to bridge the gap between macro-level policy idealism and micro-level realities on the ground. Employing a qualitative library research method with a content analysis approach toward 22 core literatures (2020–2026), the results formulate a multidimensional roadmap through integrative curriculum reconstruction (Bayani, Burhani, Irfani), institutional management based on cross-identity dialogue, and the digitization of peace narratives. Critical analysis reveals an emerging systemic vulnerability: a culture of absolute theological obedience (sami'na wa atha'na) among junior students that leaves them susceptible to manipulation within digital echo chambers. Theoretically, this study contributes by positioning religious moderation as a transformative, adaptive epistemological paradigm oriented toward universal benevolence (Rahmatan Lil 'Alamin).